2022
DOI: 10.1186/s12888-022-04487-w
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Chinese version of the biological rhythms interview of assessment in neuropsychiatry in patients with major depressive disorder

Abstract: Background Although disturbances in biological rhythms are closely related to the onset of major depressive disorder (MDD), they are not commonly assessed in Chinese clinical practice. The Biological Rhythms Interview of Assessment in Neuropsychiatry (BRIAN) has been used to evaluate disturbances in biological rhythms in MDD. We aimed to assess and confirm the reliability and validity of the Chinese version of the BRIAN (C-BRIAN) in patients with MDD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…However, due to memory bias or additional effects because of other variables ( 31 ), a more ecological assessment method should be applied for further investigations. To extend the findings from previous validation studies with clinical patients (e.g., 22 ), the present study provides support to the validation of C-BRIAN in the general public with depressive symptoms which has important implications. In addition, previous studies used global BRIAN scores to test convergent validity while the psychometric properties of the scores of each subscale were examined in the present study.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…However, due to memory bias or additional effects because of other variables ( 31 ), a more ecological assessment method should be applied for further investigations. To extend the findings from previous validation studies with clinical patients (e.g., 22 ), the present study provides support to the validation of C-BRIAN in the general public with depressive symptoms which has important implications. In addition, previous studies used global BRIAN scores to test convergent validity while the psychometric properties of the scores of each subscale were examined in the present study.…”
Section: Discussionsupporting
confidence: 76%
“…( 22 ) was translated and validated in clinical patients with MDD aged around 40 years old. Given that the age range and clinical profile of the target group in this current study was very different from previous validation study ( 22 ), it is important to translate the C-BRIAN specifically for the participants in the current study. To evaluate the severity of depressive symptoms, we used the CES-D, which has been designed to assess depressive symptomatology in the general population ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All items were scored on a 1–4 scale, with a total score ranging from 18 to 72, where higher scores indicate a higher level of biological rhythm disturbances. The Chinese version of the scale (C-BRIAN) demonstrated good reliability and validity in previous studies conducted by our research group, with a overall Cronbach’s α value of 0.898 [ 24 ].…”
Section: Methodsmentioning
confidence: 87%
“…This scale has been translated into multiple languages and has been widely used in clinical settings in countries such as South Korea, Japan, and Italy [ 21 23 ]. Research on the Chinese population with MDD has found that the Chinese version of the scale demonstrates good reliability and validity [ 24 ]. This study also reported that individuals with MDD in China exhibit a more significant degree of biological rhythm disturbances than healthy controls.…”
Section: Introductionmentioning
confidence: 99%